“El mejor legado que uno pudo dar a los hijos, ¡el estudio!”. Tierras, educación y derecho a la ciudad entre afrodescendientes e indígenas en barrios periféricos de Quito, 1980-2018 - Javier González Díez (Confluenze, 2019)
In Quito, the model of the Andean colonial city - based on the spatial concretion of a hierarchical and exclusive social structure - entered in crisis in the 80s of the 20th century. In this period, previously marginalized afro-descendant and indigenous groups start to participate in the processes of land occupation and in construction of new peripheral neighborhoods. Using stories of families from the northwest of Quito, this article explore the struggles for land and education, two elements that subaltern groups have claimed to be include, claiming their right to the city.